MEDIA FOR EDUCATION MORAL VALUE BASED ON METAPHOR (MATSAL) - Subur Subur (Institut Agama Islam Negeri Palopo, 2021)
Matsal or metaphor can be a medium in learning moral values. By using this matsal information, messages conveyed by educators can be more easily understood and accepted by students. This study aims to explore various forms of matsal in text and daily life that can be used as a medium in learning moral values. Sources of data in this study were books and real objects that exist in everyday life. The study used documentation and observation for collecting the data. Data analysis was performed by qualitative descriptive analysis. The results showed that in books and daily life, there are a lot of objects that can be used as matsal containing educational values as a medium for learning moral values; namely land, water, wind, seeds, limbs, bees, iron, and trees. Thus, matsal-based media is considered more actual and factual because it is something that happens and lives in society. Matsal is not only a medium for presenting moral teaching but also for presenting moral touching. Keywords: Media, Learning, Moral values, Matsal.